Innovation diffusion in an agricultural health center: moving information to practice. Issue 3 (3rd July 2019) - Almeida, Fabio; Cramer, Mary; Wendl, Mary; Anderson, Matthew; Rautianinen, Risto
ABSTRACT: This article presents a case study logic model-approach of the Central States Center for Agricultural Safety and Health (CS-CASH) – one of eleven federally funded Agricultural Health and Safety Centers in the United States. We used social network analysis (SNA) to examine how information generated from CS-CASH regarding respiratory personal protective equipment (PPE) use is disseminated across their network of key stakeholders and ultimately to end-users (i.e., agricultural workers). We developed a 22-item instrument based on SNA principles, and administered it to N = 49 CS CASH members and N = 158 external stakeholders. Questions focused on demographics, work setting, roles, and SNA concepts for betweenness, centrality, reciprocity, and density. Findings showed that CS-CASH has an extensive information sharing network for respiratory PPE, and there is high reciprocity with vigorous bi-directional communication; however, the network is fragmented and lacks diversity in key stakeholder roles needed to broadly diffuse information into practice. Implications are to (1) create new connections with a more diverse group of external stakeholders beyond academic and non-profit organizations, and (2) leverage primary network gatekeepers to build connections within the respiratory PPE group and with gatekeepers in the unconnected networks, thereby maximizing diffusion of information across the overall CS-CASH network. The case study has implications for evaluators and project directors looking to improve outcomes for enhanced use of respiratory PPE among end-users by working through external stakeholders who can enhance the information flow for dissemination and diffusion to practice.